2021
DOI: 10.3389/fnins.2021.675061
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Dependent Synthesis of Salsolinol in the Posterior Ventral Tegmental Area as Key Mechanism of Ethanol’s Action on Mesolimbic Dopamine

Abstract: Abnormal consumption of ethanol, the ingredient responsible for alcoholic drinks’ addictive liability, causes millions of deaths yearly. Ethanol’s addictive potential is triggered through activation, by a still unknown mechanism, of the mesolimbic dopamine (DA) system, part of a key motivation circuit, DA neurons in the posterior ventral tegmental area (pVTA) projecting to the ipsilateral nucleus accumbens shell (AcbSh). The present in vivo brain microdialysis study, in dually-implanted rats with one probe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 78 publications
0
13
0
1
Order By: Relevance
“…Morphine is, instead, the lead compound prescribed for the treatment of multiple and diverse chronic painful conditions and although developing addiction is not an issue in this case, a high rate of dependence in those who take morphine chronically has been reported with debilitating side-effects such as constipation and respiratory depression (Benyamin et al 2008 ). Notably, although the mechanism of action by which ethanol and morphine may elicit addiction is different, though not fully understood, these drugs share the ability to increase mesolimbic dopamine (DA) transmission (Di Chiara et al 2004 ; Bassareo et al 2019 , 2021 ) and induce the phosphorylation and subsequent activation of the extracellular signal-regulated kinases (ERKs) (Ibba et al 2009 ; Porru et al 2020 ; Rosas et al 2016 ; Spina et al 2015 ; Valjent et al 2004 ), two biochemical indexes critical for addiction-related behaviour in laboratory studies (Di Chiara 1999 ; Di Chiara et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Morphine is, instead, the lead compound prescribed for the treatment of multiple and diverse chronic painful conditions and although developing addiction is not an issue in this case, a high rate of dependence in those who take morphine chronically has been reported with debilitating side-effects such as constipation and respiratory depression (Benyamin et al 2008 ). Notably, although the mechanism of action by which ethanol and morphine may elicit addiction is different, though not fully understood, these drugs share the ability to increase mesolimbic dopamine (DA) transmission (Di Chiara et al 2004 ; Bassareo et al 2019 , 2021 ) and induce the phosphorylation and subsequent activation of the extracellular signal-regulated kinases (ERKs) (Ibba et al 2009 ; Porru et al 2020 ; Rosas et al 2016 ; Spina et al 2015 ; Valjent et al 2004 ), two biochemical indexes critical for addiction-related behaviour in laboratory studies (Di Chiara 1999 ; Di Chiara et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Brain-generated acetaldehyde from ethanol triggers the release of dopamine 16 via the generation of salsolinol, a product of the nonenzymatically condensation of acetaldehyde with dopamine. 13,37,38 Xie et al, 38 using the patch clamp technique, showed that salsolinol increased the firing of dopaminergic neurons, an effect blocked by both naltrexone, an antagonist of mu-opioid receptors (MORs), and gabazine, an antagonist of GABA A receptors. The release of dopamine by salsolinol, similarly to what is seen for most drugs of abuse, 15 may explain the finding that rats will self-administer both acetaldehyde and its condensation product: salsolinol.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that rodents readily self‐administer electrical pulses to the vagus nerve 9 and will also self‐administer ethanol, 10 acetaldehyde (the first ethanol metabolite) and salsolinol (a product of the nonenzymatic condensation of acetaldehyde with dopamine) into the ventral tegmental area, 11,12 indicating that all generate reinforcing effects. An increased release of dopamine in the nucleus accumbens is induced by virtually all drugs of abuse, including ethanol 13–16 and is also seen upon hypothalamic self‐stimulation 17 …”
Section: Introductionmentioning
confidence: 99%
“…Salsolinol can be metabolized by N-methyltransferase to N-methyl(R)salsolinol and subsequently via amine oxidase to 1,2-dimethyl-6,7-dihydroisoquinolinium ion. Both salsolinol and N-methyl-salsolinol are found in the cerebrospinal fluid of patients with Parkinson's disease [86][87][88].…”
Section: Other Minor Metabolites Of Ethanolmentioning
confidence: 99%